2015
DOI: 10.1016/j.neulet.2015.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of neuropathic pain behavior by amygdaloid TRPC4/C5 channels

Abstract: Pain per se may increase anxiety and conversely, anxiety may increase pain. Therefore, a positive feedback loop between anxiety and pain possibly contributes to pain and suffering in some pathophysiological pain conditions, such as that induced by peripheral nerve injury. Recent results indicate that transient receptor channels 4 and 5 (TRPC4/C5) in the amygdala have anxiogenic effects in rodents, while their role in chronic pain conditions is not known. Here, we studied whether the amygdaloid TRPC4/C5 that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…Additionally, in a mouse model for HD, activation of TRPC5 via glutathionylation was reported to underlie neurodegeneration in HD 22 . In different types of pain, TPRC1, TRPC4, and TRPC5 have been suggested to play crucial roles in mechanical hyperalgesia, neuropathic pain as well as visceral pain sensitization 23‐25,44 . In the present study, we demonstrated for the first time that chronic morphine exposure led to upregulation of TRPC1/4/5 channels in the spinal cord, and that TRPC1/4/5 deficient mice exhibited diminished analgesic tolerance and hyperalgesia.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Additionally, in a mouse model for HD, activation of TRPC5 via glutathionylation was reported to underlie neurodegeneration in HD 22 . In different types of pain, TPRC1, TRPC4, and TRPC5 have been suggested to play crucial roles in mechanical hyperalgesia, neuropathic pain as well as visceral pain sensitization 23‐25,44 . In the present study, we demonstrated for the first time that chronic morphine exposure led to upregulation of TRPC1/4/5 channels in the spinal cord, and that TRPC1/4/5 deficient mice exhibited diminished analgesic tolerance and hyperalgesia.…”
Section: Discussionsupporting
confidence: 49%
“…TRPC1/4/5 channels have been recently suggested to play crucial roles in multiple neuronal functions, including synaptic transmission and plasticity 9,15 neuronal excitability, 16‐18 neurogenesis, 19 and neurite outgrowth 20,21 . Based on these neuronal functions, TRPC1/4/5 channels were able to contribute to many human physiology and pathology, such as working memory, 9 fear, 15 Huntington's disease (HD) 22 as well as pain 23‐26 . However, it still remains elusive whether TRPC1/4/5 channels play a crucial role in the development of opioid‐induced tolerance and hyperalgesia and whether TRPC1/4/5 channels achieve this via modulation of Ca 2+ mobilization and synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…TRPC4 knock-out mice and mice treated with ML204 showed less body licking and abdominal retractions in response to mustard oil (18). TRPC4 and TRPC5 contributed to maintenance of pain hypersensitivity and neuropathy (25). TRPC1 was up-regulated and had a positive role in neointimal hyperplasia of the human saphenous vein, where it may function in partnership with TRPC5 (4, 26).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to TRPV1 and TRPA1, other TRP members have been associated to noxious sensation, including TRPM3, expressed in a number of small-diameter sensory neurons from dorsal root and trigeminal ganglia where it is involved in the nocifensive response to heat (Vriens et al, 2011), TRPV4, presented as an osmo-transducer in primary afferent nociceptive nerve fibers (Alessandri-Haber et al, 2003), TRPC1 and TRPC6, which cooperate with TRPV4 in the mediation of hyperalgesia to mechanical and hypotonic stimuli induced by inflammatory mediators (Alessandri-Haber et al, 2009), TRPV3, a channel sensitive to farnesyl pyrophosphate that is involved in the sensitivity to noxious heat (Bang et al, 2010) TRPM8, involved in cold hyperalgesia and tactile allodynia (Salat and Filipek, 2015), TRPC3, associated to the mediation of store- and receptor-operated Ca 2+ entry in DRG neurons (Alkhani et al, 2014), TRPC4, which is required for the detection or transmission of colonic visceral pain sensation, and TRPC5, which, together with TRPC4, is relevant for pain hypersensitivity and neuropathic pain (Westlund et al, 2014; Wei et al, 2015); however, the involvement of these channels in pain detection or transmission has been less characterized than that of TRPV1 or TRPA1.…”
Section: Trp Channels and Nociceptionmentioning
confidence: 99%